Ultrasonic wave propagation along the surface of a rod immersed in a liquid - FILIPCZYŃSKI, Leszek (Archives of Acoustics, 1979)
This paper describes the wave phenomena occurring in a needle used for puncture of body organs, under the simplifying assumption that this needle is an ideal elastic cylinder immersed in an ideal liquid. Investigations carried out by the author using an echo method showed that the velocity of the wave propagating in the needle immersed in water is close to the velocity of the wave propagating in water. The author has analysed the propagation of waves along a cylindrical rod of infinite length immersed in a liquid, solving the wave equations for displacement potentials in the rod surrounding liquid, taking into consideration the boundary conditions on the rod surface. It was found that it is possible for the velocity of the propagating wave to be lower than the velocity of the wave in water, with the wave being guided by the rod and the surrounding liquid layer. The characteristic equation obtained was solved numerically for a 1.5 mm diameter steel rod immersed in water at wave frequencies of 3 and 5 MHz. Stress distributions, acoustic pressure and the propagating wave displacements were determined. It can be concluded from the character of the wave that it is a surface wave. The results obtained can be used as the first approximation to the problem of wave propagation along a needle in the case where the needle wall thickness and the frequency are adequately large.